Bureaucratic Bullying in Government Organizations: Power Relations, Merit System, and Public Governance - Siti Maesaroh; Vina Karina Putri (Jurnal Ilmiah Guru Madrasah, 2026)
This article examines bureaucratic bullying as a form of unequal power relation within government organizations. Although bullying has widely been discussed in schools, workplaces, and digital environments, its operation within bureaucratic structures remains relatively underexplored, particularly in the Indonesian context. Using a qualitative conceptual-critical literature review, this article synthesizes scholarship on workplace bullying, public sector organizations, symbolic violence, disciplinary power, bureaucratic polity, civil servant neutrality, and merit-based public administration. The analysis suggests that bureaucratic bullying can be conceptualized into five main forms: institutional intimidation, factual and symbolic marginalization, bureaucratic psychological manipulation, digital bullying in organizational communication, and excessive workload allocation as a punitive mechanism. These practices tend to be enabled by hierarchical authority, bureaucratic politicization, inconsistent implementation of the merit system, and organizational cultures that normalize domination. The discussion indicates that bureaucratic bullying may weaken meritocracy, reduce public service quality, encourage a culture of silence, increase the risk of maladministration, and erode public trust in government institutions. The article argues that preventing bureaucratic bullying requires more than ethical appeals to individual leaders. It requires stronger merit protection, transparent promotion and transfer mechanisms, safe reporting channels, protection for whistleblowers and complainants, and a broader bureaucratic reform agenda that addresses internal power relations within public organizations.